2019
DOI: 10.1111/epi.14659
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injury in a community‐treated cohort of patients with epilepsy in Australia

Abstract: Summary Objective There remains a paucity of knowledge regarding specific epilepsy‐related risk factors for accidents and injuries in people with epilepsy. Injury studies in people with epilepsy are overrepresented, with tertiary based populations that are prone to bias from severe disease. This study aims to assess the contribution of epilepsy‐related risk factors to injuries in a community‐based cohort. Methods We performed a retrospective nested case‐control study on patients recruited into the Tasmanian Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Additionally, injuries during seizures were frequently observed, with a rate of up to 56% in the community-based studies. This is much higher than studies in high-income countries suggest [32,33] and also is a possible explanation for high epilepsy-associated mortality rates in LMIC [34].…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, injuries during seizures were frequently observed, with a rate of up to 56% in the community-based studies. This is much higher than studies in high-income countries suggest [32,33] and also is a possible explanation for high epilepsy-associated mortality rates in LMIC [34].…”
Section: Discussionmentioning
confidence: 63%
“…The most consistent findings regarding risk factors for injuries are occurrence of generalized convulsive seizures (focal to bilateral or generalized tonic-clonic seizures) 21,22,30,33 , but atonic seizures and ictal falls have also been associated with increased risks 21,33,34 . Intractable epilepsy, uncontrolled seizures, or high seizure frequency are also consistent risk factors for seizure-related injuries [21][22][23]31,35 . Polytherapy with AEDs was reported to be associated with increased risk in a few studies 21,31,34 although it is not clear if polytherapy is a risk factor as such or just a reflection of a more difficult to treat epilepsy with poor seizure control.…”
Section: Risk Factorsmentioning
confidence: 94%
“…In a retrospective community-based study of 819 patients with epilepsy from Tasmania, 10% reported experiencing an injury in the preceding year 22 . In the population-based childhood onset epilepsy cohort in Nova Scotia, 52 of 472 patients (11%) reported having experienced at least one serious injury during an average follow up of 24 years 23 .…”
Section: Injuries In People With Epilepsymentioning
confidence: 99%
“…Need help to identify their normal seizure pattern, when a situation is an emergency, and how to respond [30,44] Have intractable epilepsy syndromes (i.e., Lennox-Gastaut, Dravet) Have frequent nocturnal generalized tonic-clonic seizures or generalized seizure and greater risk of sudden unexpected death in epilepsy with nocturnal convulsions Require support for maintaining dignity and independence [30] and alleviating fear of having a seizure at any time [5] Require guidance for prevention of an injury [45] Are in a group that may have special concerns (e.g., young children, older adults, patients with developmental disabilities) [12] Are at high risk for seizure clusters [48] Live far from medical care or in assisted living [ [39], as well as their own burden related to epilepsy (e.g., effect on the ability to work, travel, and take part in social activities) [5] Need empowerment to address mental health issues (e.g., depression) associated with caregiving [49] 3.3.3. In the home Babysitters, grandparents, and other infrequent caregivers will benefit from an ASAP's guidance if a seizure occurs when the patient is in their care.…”
Section: Patients Whomentioning
confidence: 99%
“…It can educate and allow effective recognition of usual versus unusual patterns [39,44]. Injury risk assessment and prevention strategies [45] may be addressed by the ASAP. The ASAP may provide guidance in isolated geographic areas [37], in assisted living facilities [37], and for pre-hospital emergency personnel [39].…”
Section: When To Use the Asapmentioning
confidence: 99%